Digitalizacija (poštnih) storitev - Koritnik, Boštjan (Pravnik, 2025)
The Association of Societies for Commercial Law of Slovenia, with the support of the company Nebra, organised an online professional discussion in October 2025, titled Digitalisation of (Postal) Services – How to Use It to the Advantage of Citizens and the State? The event was held virtually, and the main guest was the Director of the Letters Division at Pošta Slovenije Mag. Karmen Lebe Grajf. The discussion was moderated by Boštjan Koritnik, former Minister of Public Administration, as the topic addressed both digitalisation and the transfer of selected administrative services from administrative units to post offices. Pošta Slovenije was named Postal Operator of the Year in 2025, partly due to its progress in digitalisation. At the same time. efforts were underway— apparently successfully—to prepare a draft law enabling the provision of certain administrative services (also) at postal outlets. The adoption of such a law, which is being prepared by the Ministry of Public Administration, would be a major step forward both for Pošta Slovenije, which is undoubtedly critical national infrastructure, and for all users of public services. Postal outlets are significantly more numerous than administrative units: there are 478 postal outlets and 58 administrative units. The closure of post offices is always a politically sensitive issue. Therefore, the optimal solution is to transfer additional tasks to post offices, thereby promoting social stability and giving citizens faster access to services.
Keywords: administrative services; Association of Societies for Commercial Law of Slovenia; digitalisation; digitalizacija; Italija; Italy; Ministrstvo za javno upravo; Ministry of Public Administration; online discussion; optimisation; optimizacija; postal outlet; Pošta Slovenije; poštna poslovalnica; Spain; spletna klepetalnica; Španija; upravne storitve; Zveza društev za gospodarsko pravo Slovenije